Pigs naturally exposed to porcine circovirus type 2 (PCV2) generate antibody responses capable to neutralise PCV2 isolates of different genotypes and geographic origins - Kurtz, Sherry; Grau-Roma, Llorenc; Cortey, Marti; Fort, Maria; Rodríguez, Fernando; Sibila, Marina; Segalés, Joaquim (BioMed Central, 2014)
Porcine circovirus type 2 (PCV2) is the essential infectious agent for PCV2-systemic disease (PCV2-SD, formerly known as postweaning multisystemic wasting syndrome) and other pathological conditions. Recent studies indicated antigenic variability amongst different PCV2 isolates and suggested that single amino acid changes within the capsid protein determine differences in the level of neutralization by specific monoclonal antibodies. The objective of the present study was to examine the cross-reactivity of PCV2 antibodies induced in the context of a natural infection against different PCV2 isolates belonging to genotypes PCV2a and PCV2b. Sera taken from several farms from animals of varying health status (PCV2-SD and age-matched healthy pigs and a set of slaughter-aged animals) were assayed for neutralizing activity against four PCV2 isolates from both predominant genotypes (PCV2a and PCV2b) and of differing geographic origins (Europe and North-America). Results showed that most of studied pigs (79 out of 82) contained neutralizing antibodies (NA) able to neutralize all four studied viral strains. Overall, pigs had significantly higher NA titres against PCV2a than against PCV2b (P< 0.001). Accordingly, studied serums were able to better neutralize Burgos390L4 and Stoon-1010 strains (PCV2a) than L-33-Sp-10-54 and MO/S-06 strains (PCV2b) (P< 0.001). No differences between capabilities of seroneutralization of viruses from different geographic origin were observed. Present data suggests that sequence differences between PCV2 isolates translate to functional antigenic differences in viral neutralization in vivo.